Ecological momentary assessment of emotional awareness: preliminary evaluation of psychometric properties - Versluis, Anke; Verkuil, Bart; Lane, Richard D.; Hagemann, Dirk; Thayer, Julian F.; Brosschot, Jos F. (Current psychology, 2021)
The Levels of Emotional Awareness Scale (LEAS) is a well-validated performance measure of trait emotional awareness (EA), which is associated with psychological and physical problems. EA is, however, expected to vary over time and we aimed to adapt the LEAS to permit the measurement of EA in daily life as a function of momentary state. Twenty-five students completed 12 ecological momentary assessments (EMAs) of EA across 2 days. The correlation between the mean EMAs of EA and trait EA, and the change over time in EA, was also examined. Findings revealed a significant positive correlation between state and trait EA. The within-person reliability was substantial, suggesting that EMAs can reliably assess EA over time across individuals. Importantly, latent state-trait analysis showed that about 50% of EA variability was due to state variance whereas only 2% of EA variability was due to trait variance. Preliminary psychometric properties suggest that the developed method allows for the measurement of EA in daily life and supports the claim that EA can be measured using both hypothetical (as in the LEAS) and real-life (using EMAs) scenarios.
Published online: 24 November 2018
Gesehen am 08.04.2021